What chance-credence norms should be. - Wroński, Leszek; Gyenis, Zalán; Cocchiaro, Mariangela Zoe (Synthese, 2022)
We show a somewhat surprising result concerning the relationship between the Principal Principle and its allegedly generalized form. Then, we formulate a few desiderata concerning chance-credence norms and argue that none of the norms widely discussed in the literature satisfies all of them. We suggest that the New Principle comes out as the best contender.